Sosialisasi dan Upaya Pencegahan Penyakit Demam Berdarah Dengue (DBD) untuk Mencegah Terjadinya Kasus Baru di Desa Jungkat: Socialization and Efforts to Prevent Dengue Hemorrhagic Fever (DHF) to Prevent the Occurrence of New Cases in Jungkat Village - Fahrurroji, Andhi; Juhardi, Jesslyn Felicia; Susanti, Diana; Anggraini, Dwi Willa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Dengue hemorrhagic fever (DHF) is a disease that is transmitted through the Aedes aegypti mosquito and is a serious threat because transmission can occur quickly in certain areas. Community Service Activities (PKM) aim to equip the community and students of Jungkat Village with information, outreach and skills about preventing DHF. Implementation of this PKM activity includes several activities such as developing socialization methods, creating DHF learning media, and carrying out pre and post tests. As a result, the average pre-test score for students was 68.20 points and the average post-test score was 76.63 points, while the average pretest score for Jungkat Village Women was 71.98 points and the average posttest score was 87.4. So, it can be concluded that there is an increase in the understanding of dengue fever in grade 7 students at SMPN 1 Jongkat and the women of Jungkat Village